Poisoning Effect Comparison of ZnCl2 and ZnSO4 on Mn‐Ce/AC Catalyst for Low‐Temperature SCR of NO. Issue 29 (4th August 2020) - Su, Zenghui; Ren, Shan; Yang, Jie; Yao, Lu; Zhou, Yuhan; Chen, Zhichao; Zhang, Tianshi
Abstract: In this study, the effect of different zinc salts (ZnCl2 and ZnSO4 ) on the deactivation of activated carbon(AC)‐based Mn−Ce catalysts and the poisoning mechanism of zinc salts on Mn−Ce/AC are comparatively studied. SEM, BET, XRD, XPS, H2 ‐TPR, NH3 ‐TPD and In‐situ DRIFT are used to characterize the physical and chemical changes of Mn−Ce/AC catalyst. The Selective Catalytic Reduction (SCR) activities of Mn−Ce/AC has a noticeable decline after loading zinc salts, and the highest NO conversion of Zn poisoning catalysts do not exceed 70 %. And the acid site is occupied by Zn 2+ on the catalyst, which affects the chemical adsorption of NH3 and hinders the formation of the intermediate ‐NH2 . Moreover, the decrease of Mn 4+, reducibility of manganese oxide and acid sites are more serious on ZnC−Mn‐Ce/AC. Besides, loading ZnSO4 can improve the content of Ce 3+ and Oβ on catalyst surface, which can mitigate the poisoning effects of ZnSO4 on Mn−Ce/AC catalyst. Hence, ZnCl2 displays a more serious poisoning effect on Mn−Ce/AC catalyst compared with ZnSO4 . Then the probable mechanism model of ZnCl2 and ZnSO4 on Mn−Ce /AC catalyst is proposed and compared. Abstract : The effect of different zinc salts (ZnCl2 and ZnSO4 ) on the deactivation of Mn−Ce/AC catalysts is comparatively studied. The decrease of Mn 4+, reducibility of manganese oxide and acid sites are more serious on ZnC−Mn‐Ce/AC. And ZnCl2 displays a more serious poisoning effect on Mn−Ce/AC catalyst compared with ZnSO4 . Finally, the probable mechanism model of ZnCl2 and ZnSO4 on Mn−Ce/AC catalyst is proposed and compared.